Carbon/Nitrogen Imbalance Associated with Drought-Induced Leaf Senescence in Sorghum bicolor - Chen, Daoqian (Public Library of Science, 2015)

(untitled) (PLoS One)
Drought stress triggers mature leaf senescence, which supports plant survival and remobilization of nutrients; yet leaf senescence also critically decreases post-drought crop yield. Drought generally results in carbon/nitrogen imbalance, which is reflected in the increased carbon:nitrogen (C:N) ratio in mature leaves, and which has been shown to be involved in inducing leaf senescence under normal growth conditions. Yet the involvement of the carbon/nitrogen balance in regulation of drought-induced leaf senescence is unclear. To investigate the role of carbon/nitrogen balance in drought-induced senescence, sorghum seedlings were subjected to a gradual soil drought treatment. Leaf senescence symptoms and the C:N ratio, which was indicated by the ratio of non-structural carbohydrate to total N content, were monitored during drought progression. In this study, leaf senescence developed about 12 days after the start of drought treatment, as indicated by various senescence symptoms including decreasing photosynthesis, photosystem II photochemistry efficiency (Fv/Fm) and chlorophyll content, and by the differential expression of senescence marker genes. The C:N ratio was significantly enhanced 10 to 12 days into drought treatment. Leaf senescence occurred in the older (lower) leaves, which had higher C:N ratios, but not in the younger (upper) leaves, which had lower C:N ratios. In addition, a detached leaf assay was conducted to investigate the effect of carbon/nitrogen availability on drought-induced senescence. Exogenous application of excess sugar combined with limited nitrogen promoted drought-induced leaf senescence. Thus our results suggest that the carbon/nitrogen balance may be involved in the regulation of drought-induced leaf senescence.